Field evaluation of Ivermectin and Mebendazole treatment against gastrointestinal parasites in stable horse. - Abdul Razak, Rohanizal; Fateh Mohamed, Bashir Ahmad; Hassan, Latiffah; Md Isa, Nur Mahiza (2011)
Deworming is one of the routine healthcare iquine management especially for stable horses. Even healthy horses harbor some adult worms and eggs and the incidence of clinical and sub0clinical diseases of horses can be minimized through controlling the gastrointestinal parasites. It was the objective of this study to determine the prevalence and species of gastrointestinal parasites in stable horses in Malaysia. In this study efficacy of ivermectin and mebendazole in reducing faecal egg count (FEC) under field condition was also evaluated. Ninety-four male and female horses of mixed breed, 11.8 ± 4.36 years of age from two stables were selected in this study. Fresh faecal samples were collected at pretratment period for initial screening and these data were used to determine the prevalence rate. Fifty more than two-year old hoses with positive epg from both stables were selected for field evaluation of mebendazole and ivermectin. Commercially available mebendazole and ivermectin paste were administered orallyaccording to manafacturer’s recommended dosage, in which the pre-treatment and day 10 post-treatment epg was utilized to determine the percentage of FEC reduction. Of the 94 fecal samples, 51 (54.3%) were positive and 3(3.2%) had fecal egg count of more than 2000 epg. There are significant association (p<0.05) between the age groups, sex and breeds. Stronglyloides westeri and cyathostome were the most prevalence worm cultures. Ivermectin showed 100% reduction while mevendazole only showed 65% reduction in FEC. This study revealed that in these stables, there is low prevalence of gastrointestinal parasites. However nine species of worms were identified. The study also showed that ivermectin had efficacy then mevendazole in reducing FEC.